2019
DOI: 10.1149/2.0161904jss
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—Control of Si3N4 Etching Kinetics and Selectivity to SiO2 by the Additives in Superheated Water

Abstract: Selective etching of Si3N4 to SiO2 is essential in the semiconductor fabrication process. In particular, as the number of alternating Si3N4/SiO2 multi-layered stacks increases, selective removal of Si3N4 without loss of SiO2 becomes difficult. In this study, the dissolution of Si3N4 was demonstrated in superheated water without addition of H3PO4, which has been widely used to etch Si3N4. The dissolution rates of Si3N4 and SiO2 in the superheated water depended strongly on the concentration of OH−, and the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…In contrast, when 0.1 M Ca­(H 2 PO4) 2 , CuSO 4 , CuCl 2 , Cu­(NO 3 ) 2 ·3H 2 O, or ZnBr 2 was added to DI water, the etching rate of Si 3 N 4 was less than 11.4 Å/min with an initial pH of solution less than 4. The results are in agreement with those of our previous study, which found that the etching rate of Si 3 N 4 in superheated water is dependent on the pH of the solution because Si 3 N 4 is etched by the nucleophilic attack of OH – …”
Section: Results and Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast, when 0.1 M Ca­(H 2 PO4) 2 , CuSO 4 , CuCl 2 , Cu­(NO 3 ) 2 ·3H 2 O, or ZnBr 2 was added to DI water, the etching rate of Si 3 N 4 was less than 11.4 Å/min with an initial pH of solution less than 4. The results are in agreement with those of our previous study, which found that the etching rate of Si 3 N 4 in superheated water is dependent on the pH of the solution because Si 3 N 4 is etched by the nucleophilic attack of OH – …”
Section: Results and Discussionsupporting
confidence: 93%
“…According to eq , the Si 3 N 4 etching rate is R Si 3 N 4 ≈ 170­[OH – ] 0.12 in this region. This reaction rate equation shows the same reaction order of [OH – ] and a similar rate constant compared with the rate equation obtained in our previous study, R Si 3 N 4 = 130­[OH – ] 0.12 (indicated by the dotted line in Figure ), where Si 3 N 4 was etched in superheated water with a wide range of OH – concentrations . In contrast, the etching rate of Si 3 N 4 is determined by the concentrations of RCOO – and OH – in superheated water when carboxylic acid is added.…”
Section: Results and Discussionsupporting
confidence: 84%
See 3 more Smart Citations